Surveillance of TB-HIV coinfection in Brazil: a space-time approach - Beatriz Almeida Santos; Caíque Jordan Nunes Ribeiro; Allan Dantas dos Santos; Álvaro Francisco Lopes de Sousa; Thayane Santos Siqueira; Lucas Almeida Andrade; Adriano José dos Santos; Shirley Verônica Melo Almeida Lima (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective To identify the epidemiological, spatial, and temporal pattern of TB-HIV coinfection in Brazil during the period from 2001 to 2020. Methods: Ecological study using space-time analysis techniques. It included cases of TB-HIV coinfection registered in Brazil from 2001 to 2020. The temporal trend analysis was performed using segmented regression by Joinpoint regression. For spatial analysis, Moran indices were calculated and choropleth maps were produced using TerraView and QGIS software. Results: A stable temporal trend was observed in the incidence rates of TB-HIV coinfection in Brazil during the analyzed period. In addition, high-risk areas for coinfection located in states in the North, Southeast, South, and Midwest regions were identified. Conclusion: There was stability in the incidence of TB-HIV coinfection in Brazil over the last 20 years and heterogeneous geographic distribution of risk areas for the condition.